The Antennapedia gene is required and expressed in parasegments 4 and 5 of the Drosophila embryo - Martinez-Arias, Alfonso (1986)
Transcripts homologous to the 5' exon of the Antp gene accumulate in parasegments 4 and 5 of the Drosophila embryo, where analysis of the cuticular phenotype of Antennapedia(-) (Antp(-)) embryos shows that there is a genetic requirement for the Antp gene. The pattern of Antp expression is different in different germ layers; the mesoderm expresses Antp only in parasegment 5; in the developing nervous system and the epidermis the pattern of expression is complex and suggests that interactions between different selector genes take place during wild-type development. Both genetic requirements and gene expression indicate that Antennapedia is the main morphological determinant in parasegment 4; in parasegment 5 it probably acts in concert with other selector genes.